Performance of ultrafiltration membranes for treatment of palm oil mill effluent - Ahmad, Mohd Azwan (2017)
The production of palm oil is the core of Malaysia economy and known globally. However, palm oil liquid waste known as palm oil mill effluent (POME) has been identified as one of the major sources of pollution in water stream throughout Malaysia. This is because POME contains high biochemical oxygen demand (BOD), high chemical oxygen demand (COD), high salt content, high suspended solid and low pH. High demand of crude palm oil has contributed to the high generation of POME and led to serious environmental issue in rivers all over the country. Based on this figure, a proper treatment method is very important in order to treat POME efficiently before releasing to the water source. Membrane separation processes are today have been adopted in many industries as its ability to treat wastewater and this includes POME. Between microfiltration (MF), nanofiltration (NF) and reverse osmosis (RO), ultrafiltration membrane (UF) was selected for this research work. UF is a cross-flow membrane process which capable of removing all microbiological species, viruses, humic materials, better rejection than MF, more applicable than NF and RO in treating POME. In this work, POME was treated with four types of ultrafiltration (UF) membranes namely EM006 (6kDa), ES625 (25kDa), FP100 (100kDa) and FP200 (200kDa). The UF membranes were studied and compared in terms of permeate quality and fouling analysis. It was observed that all UF membranes were able to treat POME and shows significant reduction in COD, total suspended solids (TSS), total dissolved solids (TDS), color, pH, and turbidity. In the comparison of the EM006, ES625, FP100 and FP200 membranes, EM006 membranes yields the highest result in terms of the foulant removal compare to other membranes with removal value of COD (82.26%), TS (95.63%), TSS (95.23%), turbidity (96.65%) and color (68.87%). Study on fouling mechanism shows that cake filtration dominates the fouling activities on surface of UF membrane, compare to standard blocking, intermediate blocking and complete blocking. The evaluation of the four membranes found that ES625 membrane are the most stable membrane used for POME treatment with a highest coefficient value of R² (0.9981) at an applied pressure of 100kPa. This is supported by the direct observation on membrane surface through SEM result and particles analysis. The relationships between multifactor in the treatment of POME using UF membranes were also evaluated by RSM. The results shows that with the application of RSM, it was able to show the correlation between measured and predicted of experimental results. The post-treatment of UF membranes after the cleaning processes were done by the coagulation methods. The characteristic of effluent after membrane washing (EMW) still shows high pollutant contents and further treatment with coagulation and flocculation with alum and Organo-floc was able to remove the pollutant to meet with limit sets for standard regulatory of POME. The findings result shows both alum and organo-floc were able to reduce the COD, TSS, color and turbidity to the standards limit sets by DOE. The best removal achieved using coagulation and flocculation method were 93% of COD, 97% of TSS and 94% of color for alum, and 96% of COD, 94% of TSS and 97% of color for organo-floc. The optimizations of the post-treatment were later performed by response surface methodology (RSM).